Design and Development of Grid-connected Quasi-Z-Source PV Inverter - Zulhani Rasin; Muhammed Fazlur Rahman; Maaspaliza Azri; Md Hairul Nizam Talib; Auzani Jidin (Institute of Advanced Engineering and Science, 2018)
An inverter system applied with the PV source typically has a problem of lower input voltage due to constraint in the PV strings connection. As a countermeasure a DC-DC boost converter is placed in between to achieve a higher voltage at the inverter DC link for connection to the grid and to realize the MPPT operation. This additional stage contributes to losses and complexity in control thus reducing the overall system efficiency. This work discussed on the design and development of a grid-connected quasi-Z-source PV inverter which has different topology and control method compared to the conventional voltage source inverter and able to overcome the above disadvantages. Modelling and performance analysis of the voltage and current controller to achieve a good power transfer from the PV source, as well sycnchronization with the grid are presented in detail. Results from both simulation and experimental verification demonstrate the designed and developed grid-connected qZSI PV inverter works successfully equivalent to the conventional voltage source inverter system.